2019
DOI: 10.1088/1757-899x/603/2/022058
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Using Clay Bricks Made from Municipal Solid Waste Incinerator (Mswi) Fly Ash

Abstract: This study deals with the effect of MSWI (municipal solid waste incinerator) fly ash on fired clay bricks. Initially, the MSWI fly ash was characterized by its chemical composition and morphology. Different ratios of the MSWI fly ash (0, 2.5, 5.0 and 7.5 % by mass) were added to the clay brick. Clay brick samples were heated on 1000 °C temperatures for 1 h. The clay brick properties of the resultant material then determined, including shrinkage (after drying, after firing), density, water absorption, effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…As an ultrafine material, MSWI-FA is also a potential substitute for clay in bricks, which should stabilize the heavy metals, reduce raw material imports, and, at the same time, conserve primary clay resources [115]. Studies have shown that fired bricks with an addition of 2.5-5 wt% treated MSWI-FA may be feasible [96,116,117].…”
Section: Potential Use Of Mswi Ashesmentioning
confidence: 99%
“…As an ultrafine material, MSWI-FA is also a potential substitute for clay in bricks, which should stabilize the heavy metals, reduce raw material imports, and, at the same time, conserve primary clay resources [115]. Studies have shown that fired bricks with an addition of 2.5-5 wt% treated MSWI-FA may be feasible [96,116,117].…”
Section: Potential Use Of Mswi Ashesmentioning
confidence: 99%
“…Šiame skyriuje aprašomos tyrimams naudotos žaliavos (molis, smėlis), jų savybės, formavimo masių paruošimo technologija, nagrinėjamų keraminių šukių technologiniai parametrai, apžvelgiami bandymo metodai, tyrimo metodikos ir bandymo įranga. Skyriaus tematika kartu su bendraautoriais paskelbti šeši straipsniai (Voišnienė et al, , 2019a(Voišnienė et al, , 2019b(Voišnienė et al, , 2020Kizinievič et al, 2019;, skaityti pranešimai šešiose tarptautinėse konferencijose.…”
Section: Medžiagos Ir Tyrimo Metodaiunclassified
“…Todėl darbe buvo naudojamas statistinis eksperimentinių duomenų apdorojimas, leidžiantis pakankami tiksliai įvertinti keraminių šukių charakteristikas, įvertinant gautų verčių išsibarstymą. (Voišnienė et al, , 2019a(Voišnienė et al, , 2019b(Voišnienė et al, , 2019c(Voišnienė et al, , 2020Kizinievič et al, 2019;, skaityti pranešimai septyniose konferencijose, paruoštas Lietuvos Respublikos patentas.…”
Section: Tyrimo Metodaiunclassified